Associations Between the Child Care Environment and Children's In-Care Physical Activity and Sedentary Time. (February 2021) - Zhang, Zhiguang; Kuzik, Nicholas; Adamo, Kristi B.; Ogden, Nancy; Goldfield, Gary S.; Okely, Anthony D.; Crozier, Mitchell; Hunter, Stephen; Predy, Madison; Carson, Valerie
Background: Child care centers are important for children's behaviors. Aims: To examine the cross-sectional associations between child care environmental characteristics and physical activity and sedentary time in children. Methods: Participants were 124 toddlers and 118 preschoolers from 19 centers in Alberta and Ontario, Canada, in the supporting Healthy physical AcTive CHildcare setting (HATCH) study. In-care physical activity and sedentary time were assessed using Actigraph accelerometers. Child care environments, including structure (e.g., resources) and process (e.g., activities) quality, were measured using three instruments: (1) the Environment and Policy Assessment and Observation and (2) the Children's Physical Environments Rating Scale, and (iii) the Movement Environment Rating Scale. Mixed models were performed to examine the associations between environmental characteristics and children's sedentary time, light physical activity, and moderate-to-vigorous physical activity. Results: A few structure quality characteristics related to child care policy and indoor environment were associated with higher physical activity and lower sedentary time in toddlers. The overall structure quality ( B = 0.04; 95% CI [0.003, 0.08]) and process quality ( B = 0.08; 95% CI [0.02, 0.15]) of the child care environment were associated with log moderate-to-vigorous physical activity in preschoolers. Specifically, structure quality characteristics of the outdoor environment and physical activity time, and process quality characteristics relevant to curriculum and pedagogy, were associated with higher physical activity and lower sedentary time in preschoolers. Discussion and Conclusion: The child care structure quality characteristics that are important for children' physical activity and sedentary behavior may vary by age group. Improving the overall process quality, in particular curriculum and pedagogy, of the child care environment, may promote more physical activity in preschoolers.